Effect of ramipril on walking times and quality of life among patients with peripheral artery disease and intermittent claudication: A randomized controlled trial - Ahimastos, A.; Walker, P.; Askew, C.; Leicht, A.; Pappas, E.; Blombery, P.; Reid, Christopher; Golledge, J.; Kingwell, B. (2013)
Importance: Approximately one-third of patients with peripheral artery disease experience intermittent claudication, with consequent loss of quality of life. Objective: To determine the efficacy of ramipril for improving walking ability, patient-perceived walking performance, and quality of life in patients with claudication. Design, Setting, and Patients: Randomized, double-blind, placebo-controlled trial conducted among 212 patients with peripheral artery disease (mean age, 65.5 [SD, 6.2] years), initiated in May 2008 and completed in August 2011 and conducted at 3 hospitals in Australia. Intervention: Patients were randomized to receive 10 mg/d of ramipril (n=106) or matching placebo (n=106) for 24 weeks. Main Outcome Measures: Maximum and pain-free walking times were recorded during a standard treadmill test. The Walking Impairment Questionnaire (WIQ) and Short-Form 36 Health Survey (SF-36) were used to assess walking ability and quality of life, respectively. Results: At 6 months, relative to placebo, ramipril was associated with a 75-second (95% CI, 60-89 seconds) increase in mean pain-free walking time (P<.001) and a 255-second (95% CI, 215-295 seconds) increase in maximum walking time (P<.001). Relative to placebo, ramipril improved the WIQ median distance score by 13.8 (Hodges-Lehmann 95% CI, 12.2-15.5), speed score by 13.3 (95% CI, 11.9-15.2), and stair climbing score by 25.2 (95% CI, 25.1-29.4) (P<.001 for all). The overall SF-36 median Physical Component Summary score improved by 8.2 (Hodges-Lehmann 95% CI, 3.6-11.4; P=.02) in the ramipril group relative to placebo. Ramipril did not affect the overall SF-36 median Mental Component Summary score. Conclusions and Relevance: Among patients with intermittent claudication, 24-week treatment with ramipril resulted in significant increases in pain-free and maximum treadmill walking times compared with placebo. This was associated with a significant increase in the physical functioning component of the SF-36 score. Trial Registration: clinicaltrials.gov Identifier: NCT00681226 ©2013 American Medical Association. All rights reserved.